(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
After the change that happened in the work environment and its development and as result of the this effects on the environment, it become clear that the companies has to care for the environment because the increase in the pollution ratios in all of its sort, the companies started to care so we did found in fact some states has obliged the companies to use industrial methods that produces less pollution as much, the oil companies especially the gas companies which consume much gas by burning it or using conventional tools in its eradication or transportation which causes much gas waste, and it increases the environmental pollutions and the waste in limited natural resources, so we did this study to show that the companies could gain profit through protecting the environment, in order to achieve the sustainable development to the next generations.